2011
DOI: 10.1007/978-1-4419-7548-5
|View full text |Cite
|
Sign up to set email alerts
|

Digital System Test and Testable Design

Abstract: ), except for brief excerpts in connection with reviews or scholarly analysis. Use in connection with any form of information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed is forbidden. The use in this publication of trade names, trademarks, service marks, and similar terms, even if they are not identified as such, is not to be taken as an expression of opinion as to whether or not they are subject to proprietary rights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…In the context of ATPG [18], sets of don't care conditions are usually divided into observability don't cares (ODC) and controllability don't cares (CDC). The former denotes lines that do not influence the primary outputs (independent from the current assignment to the primary inputs), and the latter identifies line values that can not be justified and are therefore illegal under any assignment to the primary inputs.…”
Section: A Justification-based Partial Model Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of ATPG [18], sets of don't care conditions are usually divided into observability don't cares (ODC) and controllability don't cares (CDC). The former denotes lines that do not influence the primary outputs (independent from the current assignment to the primary inputs), and the latter identifies line values that can not be justified and are therefore illegal under any assignment to the primary inputs.…”
Section: A Justification-based Partial Model Extractionmentioning
confidence: 99%
“…We show that don't care reasoning on full candidate models to extract partial candidate models subsequently reduces the cost for consistency checking by focusing on the relevant parts of the formula, only. Motivated by dual propagation techniques in the context of quantified boolean formulas (QBF) [15] [16], we propose an optimization of the lemmas on demand procedure in [19] and compare our approach to a technique based on justification heuristics in ATPG [18]. We implemented both techniques in our SMT solver Boolector and analyse the results in comparison to the version of Boolector that won the QF AUFBV track of the SMT competition 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Fault models describe physical defects and system failures, as well as the input patterns that expose them. Thus, the fault models are suitable for further modeling and testing, while error models describe the effects of defects on the system's outputs, and they are useful for on-line error detection [3].…”
Section: Introductionmentioning
confidence: 99%
“…Typical yield models are mathematically and/or simulation based. However, in order to provide an accurate estimate of the yield, the model must account various considerations [3]. Redundancy was first introduced for hardware fault-tolerance with Triple Modular Redundancy (TMR) in which the original nonfault-tolerant circuit module was triplicated with majority voting circuits added at the outputs of the triplicated circuit modules [4].…”
Section: Introductionmentioning
confidence: 99%
“…But authors in [1] have shown that these fault models do not present enough fault coverage, and proposed MDSI fault model with higher coverage. An accepted cost effective way of testing SoCs is the IEEE std.1149.1 boundary scan standard [2]. One of the drawbacks of using this method is the inability of detecting timing related faults.…”
Section: Introductionmentioning
confidence: 99%